2020
DOI: 10.1080/17461391.2019.1704068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the grip width on the reliability and magnitude of different velocity variables during the bench press exercise

Abstract: This study aimed to compare the within-session reliability and magnitude of velocity variables recorded against a range of submaximal loads during the bench press (BP) exercise performed in a Smith machine using different grip widths. Sixteen physically active men (BP one-repetition maximum [1RM] relative to body mass = 1.01 ± 0.19 kg•kg −1 ) were randomly tested on 4 sessions using a close grip width (100% of biacromial width), medium grip width (150% of biacromial width), wide grip width (200% of biacromial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
8
1
Order By: Relevance
“…These findings are in line with those previously demonstrated by Wilk et al [25], who did not find significant differences between the narrow (95% of the biacromial width) and wide (200% of the biacromial width) grip widths for the XRM completed against the grip-specific 75% 1RM loads during the free-weight BP exercise. It has previously been suggested that changes in BP grip width can affect 1RM performance [19][20][21] and kinetic and kinematic outputs [22][23][24]. However, based on the findings by Wilk et al [25], and the results of the present study, it seems that the grip width might not affect the total repetition volume or the repetition volume before exceeding a pre-determined VLT.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…These findings are in line with those previously demonstrated by Wilk et al [25], who did not find significant differences between the narrow (95% of the biacromial width) and wide (200% of the biacromial width) grip widths for the XRM completed against the grip-specific 75% 1RM loads during the free-weight BP exercise. It has previously been suggested that changes in BP grip width can affect 1RM performance [19][20][21] and kinetic and kinematic outputs [22][23][24]. However, based on the findings by Wilk et al [25], and the results of the present study, it seems that the grip width might not affect the total repetition volume or the repetition volume before exceeding a pre-determined VLT.…”
Section: Discussioncontrasting
confidence: 64%
“…Subjects started the task lying supine on a flat bench, with their feet resting on the floor, their elbows fully extended, and their hands placed on the bar using either a narrow, medium, wide, or self-selected grip width. From this position, they lowered the bar in a controlled manner until it made contact with the chest, held this position for approximately two seconds, and then lifted the bar as fast as possible until their elbows reached full extension [23,24]. The position of the bench was adjusted so that the vertical projection of the bar corresponded to each subject's intermammary line.…”
Section: Description Of the Bp Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, training effects can be modulated by the range of motion (ROM), defined as the degree of movement that occurs at a specific joint during the execution of an exercise 20 . In daily practice, the ROM can be modified by altering the body posture 21 or grip width, 22,23 using external materials like security bars or wood boards 24,25 or by voluntarily reducing the degree of movement at the beginning or end of the execution 26,27 28 On this matter, the specific ROM influences different biomechanical aspects that affect, among others, the development of force, motor units activation, and dynamic joint stability 25,29 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Note that a range of movement of 40 cm is a plausible displacement for resistance training exercises, such as the squat or bench press. 17 The isokinetic velocity was delivered by the FEMD. An elastic band was attached to the cable of the FEMD and the researcher held the band in position before the software started recording the data.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%